The effect of endurance training on serum hs-Creative protein as an inflammatory predictor of cardiovascular disease in untrained men - حشمت الله پارسیان; خسرو ابراهیم; حجت اله نیک بخت; فتانه خانعلی (Shahid Beheshti University, 2009)
The effect of endurance training on serum hs-Creative protein as aninflammatory predictor of cardiovascular disease in untrained menAbstractPurpose: The purpose of this study was to determine the effect of endurance training on hscreativeprotein (hs-CRP) as a predictor of cardiovascular disease. Methods: For this purpose, 30healthy male students from Science and Research Azad University of Tehran branch were selectedand divided randomly into two equal groups (endurance training and control). Endurance grouptrained for 12 weeks, 3 times a week at particular intensity and duration. Two blood samples weretaken before and after training hs-CRP after training. Hs-CRP was measured using ELISA kits andimmunoturbidometric assay. Results: Data were analyzed using paired and independent t-test atP<0.05. The result showed that hs-CRP levels decreased significantly (P=0.001) after 12 weekstraining. Conclusions: Generally, it could be concluded that regular endurance training could behelpful in reducing the risk of cardiovascular disease through lowering the serum hs-CRP levels.